EFEITO DE CICLOS DE POLIMERIZAÇÃO EM MICRO-ONDAS SOBRE PROPRIEDADES FÍSICAS, QUÍMICA E BIOLÓGICA DE RESINAS ACRÍLICAS PARA BASE DE PRÓTESE - Figuerôa, Rosana Marques Silva (2016)
The aim of this study was to determine a microwave polymerization cycle that resulted in adequate physicomechanical and biological properties for the denture base acrylic resins polymerized in water bath (Vipi Cril-VC, VIPI®) or processed by microwave energy (Vipi Wave-VW, VIPI®). The evaluated polymerization cycles were: 1) WB (water bath) = (65ºC during 90 min + boiling during 90 min), recommended cycle for the VC resin; 2) M630/25 = 10 min at 270 W + 5 min at 0 W + 10 min at 360 W, recommended cycle for VW resin; 3) M650/5 = 5 min at 650 W; 4) M550/3 = 3 min at 550 W. The following properties were evaluated: degree of conversion (n=6), cytotoxicity (n=9), porosity (n=10), water sorption and solubility (n=10), and surface roughness and color stability (n=5) after immersion in potential colorant beverages and simulated toothbrushing. Data were submitted to analysis of variance ANOVA-2 way followed by Bonferroni’s test for degree of conversion and color stability, ANOVA-2 way for porosity and cytotoxicity, ANOVA-2 way followed by HSD Tukey’s test for water sorption and solubility, and ANOVA-3 way followed by Bonferroni’s test for surface roughness (α=0.05). For VC resin, there was no significant difference among the groups for degree of conversion. For VW resin, the lowest degree of conversion values appeared in the M630/25 and M650/5 cycles (P<0.05). Degree of conversion values ranged from 66.9 to 85.9%. There was no difference between the materials and experimental groups for cytotoxicity and all conditions resulted in non-cytotoxic effects. Porosity mean values below 1.52% with no significant difference among groups for both materials were observed. Resins showed water sorption and solubility values without a significant difference. The highest water sorption (2.43%) and solubility (0.13%) values were obtained for WB and M550/3, respectively (P<0.05). After immersion in coffee, M550/3 and WB groups of VC resin showed the highest and the lowest roughness values, respectively (P<0.05). There was also an increase in roughness of M550/3 group after immersion in wine (P<0.05). For VW resin, M650/5 group presented rougher surface after immersion in coffee (P<0.05). There was no difference in color among cycles for VW resin and VC resin showed more changes (P<0.05). All medium values were classified as acceptable, exception for VW resin (M630/25 group) which presented NBS=4.88 after immersion in wine. Vipi Cril conventional resin can be polymerized in microwave without impairment to the evaluated properties. According to the obtained results, the better experimental condition was the microwave polymerization at 650 W for 5 min for Vipi Cril.